Temperature changes of the exciton transition energy in lead di-iodide nanofilms - Pugantseva, O.V.; Kramar, V.M.; Fesiv, I.V.; Kudryavtsev, O.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Adduced in this work are the results of theoretical investigations devoted to
the influence of spatial confinement effects, self-polarization of heterojunction planes
and exciton-phonon interaction on values of the exciton transition energy in lead diiodide
nanofilms placed into dielectric ambience (glass or polymer). The heterojunction
is considered to be unloaded, nanosystem is modeled with an infinite deep quantum well
and characterized by an essential difference between dielectric permeabilities in both
sides of the heterojunction. Calculated in the work are dependences of the exciton energy
on the nanofilm thickness and temperature. The results of calculations are in accordance
with the known data of experimental measurements.